Patterns of artificial tanning use and the perceived risk of skin cancer by high school students in a midwestern city - Johnson, Angela Marie (My University, 1996)
This prospective prevalence study was designed to identify patterns of artificial tanning use and determine the perceived risk of skin cancer among adolescents at two high schools. Four hundred and sixty subjects completed a 2 part, 41-item questionnaire. Results indicated that females were significantly (< .05) more knowledgeable of risks of artificial tanning devices (ATD), and used ATD's more than males (chi-square value = 29.738). Similar results indicated that juniors were more knowledgeable (p < .05) and used A.T.D's more frequently (chi-square value = 21.121) than freshmen subjects. Perceptions of the seriousness of skin cancer varied significantly (p < .05) between female and male subjects. This was not true between freshmen and junior subjects (p > .05). All subjects varied significantly in the distribution of perceptions regarding 1) how treatable skin cancer is, 2) how preventable skin cancer is, 3) how likely subjects will get skin cancer, and 4) how often they think about skin cancer. There were no significant differences (p > .05) between either group (e.g., females vs. males or freshmen vs. juniors) regarding reported number of visits to tanning salons, length of tanning session, and use of eye protection. There were also no significant associations (p > .05) between subjects' perception of getting skin cancer in the future and knowledge of tanning booths, length of tanning session, and use of eye protection. Recommendations are made for future research.
Keywords: High school students -- Middle West -- Attitudes.; Skin -- Cancer -- Prevention.